The comparative of free energy binding between Pyrimethamine-pDHFR double mutant and Pyrimethamine-pDHFR quadruple mutant: Structure-based approach - Abdjan, Muhammad Ikhlas; Aminah, Nanik Siti; Kristanti, Alfinda Novi; Takaya, Yoshiaki; Siswanto, Imam (Universitas Airlangga, 2022)
Structure-based was performed to understand the mechanism inhibition of pyrimethamine (CP6) against Plasmodium Falciparum mutants at the molecular level. A molecular docking process was carried out to obtain the initial conformation of each system. The data showed in the form of RMSD values, hydrogen bonds, and grid scores. The results show that the RMSD value in the redocking process meets the criteria of the CP6-1J3J and WRA-1J3K complexes with a value of â‰¤ 2 í…. Several hydrogen bonds bind to receptor-active sites, including Ile14, Asp50, Ile164, and Asn108. Additionally, the grid score (kcal/mol) binds well on the active site: CP6-1J3J (-46.86), WRA-1J3K (-65.40), and CP6-1J3k (-44.71). Furthermore, molecular dynamics simulation was carried out to determine the free energy (âˆ†Gbind) of each complex using the MM/GBSA approach. The results show âˆ†Gbind (kcal/mol) in each complex, namely CP6-1J3J (-28.24), WRA-1J3K (-36.62), and CP6-1J3k (-24.23). Information on this research was expected to provide molecular insight into pyrimethamine as an antimalaria inhibitor.